Foreword to the Special Section on Smart Tools and Applications in Computer Graphics 2017. (August 2018) - Giachetti, Andrea; Pingi, Paolo; Stanco, Filippo
Highlights: Extended best papers from Smart Tools and Apps in Computer Graphics 2018. Illustrative visualization. 3D gesture retrieval. N-dimensional segmentation boundaries smoothing. Graphical abstract: